The Influence of Leadership Ethics, Accounting Understanding, Utilization of Accounting Information Systems, Internal Control Systems, and Organizational Culture on the Quality of Financial Statements of Savings and Loan Cooperatives in Tabanan District - PUTRA, M Doni Permana; BHEGAWATI, Desak Ayu Sriary; PANDE, Dinda Samhita (PT. Keberlanjutan Strategis Indonesia, 2025)
Purpose:This study aims to analyze the effect of leadership ethics, level of accounting understanding, utilization of accounting information systems, internal control systems and organizational culture on the quality of financial statements at KSP in Tabanan District, Tabanan Regency.Methodology:The population in this study were all employees who worked at KSP Tabanan District, Tabanan Regency, namely 225 employees. The sampling method used a purposive sampling method with 135 employees. The data analysis technique used is multiple linear regression analysis.Findings:The results of this study indicate that leadership ethics, level of accounting understanding, and organizational culture do not affect the quality of financial reports in savings and loan cooperatives. At the same time, the use of accounting information systems and internal control systems has a positive effect on the quality of financial reports in savings and loan cooperatives in Tabanan District, Tabanan Regency.Implication:Expanding the literature on factors that influence the quality of financial reports in non-bank financial institutions, especially savings and loan cooperatives.